Early Pandya Simhavahini and Sapta Matrka Sculptures in the Far South of India - Rajarajan, R. K.K. (Religions of South Asia, 2016)
The Early Pandyas and the Pallavas were contemporaries, dated c. 550-850 ce. South Indian art of this period falls under the dynastic lineages of Western Calukyas, Eastern Calukyas, Pallavas, Early Pandyas and Rastrakutas. The iconographical idioms familiar in their arts are Simhavahini and Sapta Matrkas. Simhavahini to an extent was popularized by the Western Calukyas, as shown in the rock-cut temples of Ellora. The Pallava structural temples of Kancipuram include a number of images. An analogous iconographic theme is Kalaiamarcelvi/Mrgavahini. Sapta Matrkas was a theme popularized by the Guptas. As far as our present knowledge goes, the geographical range of Simhavahini extends southwards as far as Kancipuram, and the Matrkas go further southward, as far as Parankunram. However, as a breakthrough we discovered images of Simhavahini and the Matrkas in a small hamlet at Veppankulam in the Srivilliputtur circle, Tamilnadu. Kalaiamarcelvi had so far come to light only in northern Tamilnadu. The discovery of Simhavahini and the Matrkas in the far south is crucial because it expands the map of these divinities from Udayagiri in the north to Srivilliputtur in the far south. Another important discovery is that the Simhavahini of the present study combines features typical of the Deccan (e.g. the lion vehicle) and the far south (e.g. standing on the head of a buffalo). Such images are found rarely in the north, and seem to be rooted in Tamil cultural traditions.